Anti-aging drugs : (Royal Society of Chemistry, 2017)
This book provides an overview of current research aimed to search for life-extending medications and describes pharmacological aspects of anti-aging medicine. Readers are introduced to the fascinating historical background of geroprotection in the first chapter. In-depth information on models for investigating geroprotective drugs precedes a section covering anti-aging properties of pharmaceutical compounds, such as calorie restriction mimetics, autophagy inducers, senolytics and mitochondrial antioxidants. Finally, strategies to translate discoveries from aging research into drugs and healthcare policy perspectives on anti-ageing medicine are provided to give a complete picture of the field. A timely and carefully edited collection of chapters by leading researchers in the field, this book will be a fascinating and useful resource for pharmacologists, gerontologists and any scientifically interested person wishing to know more about the current status of research into anti-aging remedies, challenges and opportunities.